'Invisible minorities' and 'hidden diversity' in Saint-Petersburg's linguistic landscape. (September 2019) - Baranova, Vlada; Fedorova, Kapitolina
Abstract: The article deals with representation of labour migrants' languages in St. Petersburg's linguistic landscape. The data analyzed in the article were gathered through fieldwork (in 2016–2017) in different districts of the city. The communication between the majority and ethnic minorities is conducted only in Russian, both in official and in informal exchanges, such as between commercial agencies and non-Russian speakers. Even in places with no official regulation, non-Russian languages' use is significantly rare and occurs predominantly in the frame of in-group communication. Only two languages, Chinese and Uzbek, occasionally can be used in advertisements but targeted exclusively to minorities. Both official language policy and attitudes of ethnic majority tend to ignore actual diversity of the city, maintaining urban monolingual 'façade'. Highlights: Poor visibility of migrants' languages in the LL of St. Petersburg is evident. When migrants' languages do become visible in LL it is predominantly internal communication. Minority languages are only occasionally used for 'ethnic marketing' purposes. There is an important difference between written communication in 'open' and 'closed' spaces. Russian speaking majority tends to ignore linguistic needs of migrants.